The 5M Approach to Analyse RME Downtime Factors in the Registration and Admission Unit at Udayana Type II Military Hospital, Denpasar - Ni Wayan Sriluna Astari; Made Wahyu Aditya; A.A Gde Oka Widana (LPPM Universitas Dhyana Pura, 2026)
Downtime in the Electronic Medical Records (EMR) system at Udayana Level II Military Hospital has reduced the effectiveness of outpatient services. System disruptions in the registration and admission units have led to long queues and increased the risk of medical errors. This study aims to analyze the causes of this downtime using the 5M management approach (Man, Money, Material, Machine, Method). A descriptive qualitative method was employed. Data were collected through direct observation and in-depth interviews with key informants in the relevant units. Interview guidelines were used as instruments to explore operational constraints in each of the 5M elements. The results revealed that downtime was caused by limited digital competencies of staff (Man), outdated computer specifications (Machine), and network disruptions due to adverse weather conditions (Material). Additionally, inefficient manual transition workflows (Method) and bureaucratic obstacles in the implementation of the IT budget (Money) were identified as critical contributing factors contributing to the disruptions. That the dominant factors causing downtime lie in the Man, Machine, and Material aspects, supported by the Method and Money factors; therefore, integrated improvements are needed to enhance system reliability and service quality. It is recommended that management streamline the bureaucracy surrounding equipment repairs, upgrade hardware, provide UPS systems, and offer self-mitigation training to staff to ensure uninterrupted service.